Metodologia científica na educação básica: as práticas de ensino e a formação do estudante nas escolas de ensino médio em Parintins (AM) - Ferreira, Hanna Glenda de Souza (Brasil, 2025)
Scientific Methodology is generally found in the educational spaces of Higher Education, composing the curriculum of introductory disciplines of all academic courses. However, it is a useful and safe tool for the development of a mature attitude towards scientific knowledge, whether instrumental, technical or logical, aiming at learning (Severino, 2000), in school stages of Basic Education. The main objective of the work is to analyze the Scientific Methodology inserted in the teaching practices of Basic Education and the contributions to the education of High School students in Parintins (AM), articulating scientific-methodological knowledge with the knowledge developed in teaching practices. Using a qualitative approach, a Field Research was carried out in High School schools, interviews with teachers and a questionnaire with students. Although Scientific Methodology is part of some teaching practices for scientific initiation in the participating schools, students express the need and desire to acquire this knowledge, since its absence creates gaps in their education: problems related to writing, lack of scientific rigor in the preparation of papers, lack of articulation with scientific knowledge and/or systematization and reasoning according to necessary procedures and techniques, among others. The need for CM to be part of the curricular teaching practices was confirmed, since its contribution has a qualitative impact on the student's education. Bringing the relevance of this area of ​​knowledge to the school debate favors the reader's critical capacity, impacts scientific rigor and the quality of knowledge production.